The effect of l-arginine supplementation on amelioration of oxygen support in severe COVID-19 pneumonia. (December 2022) - Muralidharan, Jananee; Kashyap, Sindhu; S, Poorvikha; Jacob, Mathew; Ollapally, Anjali; Idiculla, Jyothi; Raj, John Michael; Thomas, Tinku; Kurpad, Anura V.
Summary: Background & aims: l -Arginine (l -Arg) has been shown to help reduce respiratory support requirements in coronavirus disease 2019 (COVID-19), in an Italian study. We investigated the effect of l -Arg supplementation on the reduction in respiratory support for patients with severe COVID-19 pneumonia in an Indian population. Methods: A parallel-group, triple-blinded, randomized controlled trial (RCT) was conducted on patients with severe COVID-19 pneumonia on oxygen (O2 ) support. Patients received either 3 g of oral l -Arg or placebo, daily under supervision, until they were off O2 support, or for a maximum of 10 days, whichever was earlier. The primary outcome was cessation in O2 support. Other outcomes were time to cessation of O2 support, duration of hospitalization, and incidence of adverse thrombotic events. Results: We did an intention-to-treat analysis on 74 patients who were randomized into l -Arg (n = 38) or placebo group (n = 36). There were no significant differences between the two groups in the outcomes. At end of the study, 28 patients (73.6%) in l -Arg and 26 patients (72.2%) in the placebo group were weaned off oxygen support. The median number of days to the cessation of O2 support estimated using Kaplan Meir survival analysis, was 3 days in the l -Arg group (95% confidence interval [CI]: 1.2, 4.7) and 5 days in the placebo group (95% CI, 4.1, 5.8); P = 0.27. Conclusion: In this group of patients with severe COVID-19 pneumonia, l -Arg supplementation did not show any significant difference in outcomes when compared to placebo supplementation.